The service quality at collection counter in Syarikat Sesco Berhad, Sibu Sarawak / Peter Sylverter Atim - Sylverter Atim, Peter (2009)
This paper is prepared to identify the level of customers’ satisfaction at the Collection Counter of Syarikat SESCO Berhad, Sibu. Then, analyze the data collected in order to come out with the specific results, such as level of current satisfaction and suggested recommendations for improvement. The results are useful to assist the management of the company to improve the areas which found to be weak and where necessary need to construct and develop the new areas for the better ofthe company.